The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.jped.2017.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Being a mother of preterm multiples in the context of socioeconomic disadvantage: perceived stress and psychological symptoms

Abstract: The results of the present study have important implications for practice. Mothers of preterm multiples are at higher risk to present mental health difficulties, in comparison to mothers of singletons, especially when exposed to socioeconomic adversities. The development of psychosocial intervention programs and public policies are of decisive importance in helping mothers of multiples adjust to parenthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
1
8
0
1
Order By: Relevance
“…The use of developmental intervention services also was associated with intraindividual cognitive decline, although this finding was attenuated after adjusting for family clustering. In line with prior reports, 13,54 preterm multiples were more likely to have received interventions than singletons, potentially due higher rates of delay at 2 years.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The use of developmental intervention services also was associated with intraindividual cognitive decline, although this finding was attenuated after adjusting for family clustering. In line with prior reports, 13,54 preterm multiples were more likely to have received interventions than singletons, potentially due higher rates of delay at 2 years.…”
Section: Discussionsupporting
confidence: 87%
“…As prior VPT cohorts 9,10 had fewer single parent, ethnic minority, and low socio-economic families than typical American cohorts, 8,11 previous findings may not generalize to more disadvantaged samples 12 and have not accounted for shared variance in social background among preterm multiples despite these families experiencing greater social hardships and parenting stress. 13 Parenting stress and family dysfunction are associated with VPT birth 14 and social risk 15 yet the extent to which these factors underlie developmental variation among VPT children is unclear. In addition, maternal intelligence co-varies with education and occupation status 16,17 and predicts cross-sectional cognitive, language and motor outcomes in term and VPT children.…”
mentioning
confidence: 99%
“…Baptista et al studied mothers whose ex-preterm infants were now one year of age [Baptista, 2018]. According to this study, mothers of preterm multiples were more like to experience stress than their singleton counterparts.…”
Section: Mothers Of Preterm Multiple Infants Compared To Mothers Of P...mentioning
confidence: 99%
“…They also reported that mothers of preterm multiples, when facing poor socioeconomic circumstances, were likely to experience higher levels of psychological symptoms. These psychological symptoms were assessed using the BSI (brief symptom inventory), which included anxiety [Baptista, 2018].…”
Section: Mothers Of Preterm Multiple Infants Compared To Mothers Of P...mentioning
confidence: 99%
See 1 more Smart Citation